Studi Literatur Pengaruh Penjualan Kendaraan Bermotor Terhadap Pertumbuhan Ekonomi di Indonesia dan Implikasinya Bagi Pengembangan Model Kemitraan Pemerintah-Swasta di Kabupaten Bekasi - Yusuf Hamdani (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
Regional economic growth requires indicators that can capture economic dynamics more quickly and responsively than annual official statistics. Vehicle sales represent one of the most potential sectoral indicators because they reflect consumer purchasing power, mobility, and the development of the automotive industry. This study aims to examine the relationship between motor vehicle sales and economic growth in Indonesia and to identify its implications for the development of public–private partnership (PPP) models in Bekasi Regency. The research adopts a Study Literature, which includes identification, screening, eligibility, and inclusion stages. The findings show that motor vehicle sales have a positive and consistent relationship with economic growth, influenced by macroeconomic variables such as GDP, inflation, and exchange rates, as well as non-macroeconomic factors including consumer behavior and technological developments. The discussion highlights that automotive indicators can serve as early signals of economic shifts and may be utilized in PPP planning, particularly in industrial regions such as Bekasi Regency. This study concludes that motor vehicle sales function as a relevant sectoral indicator to support regional development decision-making.